Analyzing Financial Performance at Bank Sulselbar Using Activity and Investment Ratios - Umsini, Ratna Widyawati; Nurfadhilah, Nurfadhilah; Darwis, Darwis; Damira, Damira; Amiruddin, Muhammad Majdy (Department of Sharia Financial Management, Institut Agama Islam Negeri Sultan Amai Gorontalo, Indonesia, 2024)
The financial condition of Bank Sulselbar has shown fluctuations in recent years. This study aims to evaluate the bank's financial performance through the Activity Ratio and Investment Ratio. A quantitative research method uses financial statements from 2018-2022 as the sample. The secondary data is sourced from the published financial reports of Bank Sulselbar. The findings indicate that: (1) Based on the Activity Ratio, specifically the Fixed Assets Turnover, Bank Sulselbar's financial performance is good, as the FAT results over five years exceed the measurement standard. However, the total assets turnover is rated poorly since its value did not meet the measurement standard during the same period. (2) Regarding the Investment Ratio, the Return On Investment is deemed unsatisfactory, as the five-year calculations reveal that the ROI has not surpassed the required measurement standard. Conversely, the Return On Equity calculations for five years are classified as very good, meeting the established measurement criteria.